Physician knowledge and attitudes towards screening and referral for obstructive sleep apnea: a mixed methods study in a tertiary care hospital - Nicole Beck; Aref G Ebrahim; Samarth Shetty; Salim Afshar; Alben Sigamani; Paul Salins (Journal of Global Health Reports)
# Background Cardiovascular diseases have risen to be the top cause of mortality and morbidity globally and at a faster pace in developing countries. Obstructive sleep apnea (OSA) is an established common denominator, severely underdiagnosed, and a potentially modifiable risk factor for non-communicable diseases (NCDs). Our study is a mixed methods evaluation of knowledge and attitudes among physicians about OSA, from a tertiary care hospital in Bangalore, South India, and how it is integrated into their practice of screening and referral for OSA diagnosis and treatment.